Jane Austen’s Comic Vision in her Art of Characterization with Special Reference to ‘Pride and Prejudice’ - Priydarshi, Ashok Kumar (Journal of Advanced Research in English & Education, 2021)
Characterization is a literary device that is used step-by-step in literature to highlight and explain the details about a character in a story. In other words, characterization is the representation of persons in narrative and dramatic works. The term character development is sometmes used as a synonym. This representation may include direct methods like the attribution of qualities in description or commentary and indirect [dramatic] method invitie readers to infer qualities from characters’ action, dialogue, or acceptance. Such a personage is called a character. The range of Jane Austen’s characters is narrow but humour touches all her best characters. How to cite this article:  Priydarshi AK. Jane Austen’s Comic Vision in her Art of Characterization with Special Reference to ‘Pride and Prejudice’. J Adv Res Eng & Edu 2020; 5(2): 5-7. DOI: https://doi.org/10.24321/2456.4370.202005